Oncogenic Integration of Nucleotide Metabolism via Fatty Acid Synthase in Non-Hodgkin Lymphoma - Ravi, Dashnamoorthy; Beheshti, Afshin; Abermil, Nasséra; Lansigan, Frederick; Kinlaw, William; Matthan, Nirupa R.; Mokhtar, Maisarah; Passero, Frank C.; Puliti, Patrick; David, Kevin A.; Dolnikowski, Gregory G.; Su, Xiaoyang; et al. (Frontiers in Oncology, 2021)
Metabolic dysfunctions enabling increased nucleotide biosynthesis are necessary for supporting malignant proliferation. Our investigations indicate that upregulation of Fatty Acid Synthase (FASN) and de novo lipogenesis, commonly observed in many cancers, is associated with nucleotide metabolic dysfunction in lymphoma. Results from our experiments showed that ribonucleotide and deoxyribonucleotide pool depletion, suppression of global RNA/DNA synthesis, and cell cycle inhibition occurred in the presence of FASN inhibition. Subsequently, we observed FASN inhibition caused metabolic blockade in the rate-limiting step of oxidative branch of Pentose Phosphate Pathway (oxPPP) catalyzed by Phosphogluconate Dehydrogenase (PGDH). Further, we determined that FASN inhibitor treatment resulted in NADPH accumulation and inhibition of PGDH enzyme activity. NADPH is a cofactor utilized by FASN, is also a known allosteric inhibitor of PGDH. Through cell-free enzyme assays consisting of FASN and PGDH, we delineated that PGDH catalyzed ribulose-5-phosphate (R5P) synthesis is enhanced by FASN presence and is suppressed by increasing concentrations of NADPH. Additionally, we observed that FASN and PGDH were colocalized in the cytosol. Results from these experiments led us to conclude that NADP-NADPH turnover and reciprocal stimulation of FASN and PGDH catalysis are involved in promoting oxPPP and nucleotide biosynthesis in lymphoma. Finally, transcriptomic analysis of non-Hodgkin’s lymphoma (n=624) revealed increased expression of genes associated with metabolic functions interlinked with oxPPP, while expression of genes participating in oxPPP remained unaltered. Together, we conclude that FASN-PGDH enzymatic interactions are involved in enabling oxPPP and nucleotide metabolic dysfunction in lymphoma tumors.